The Application of Biologically Active Components Derived from Mineral, Synthetic, Phyto- and Organic Sources for Developing Local Hemostatic Agents: Historical Traditions and Contemporary Advancements - Abramov, S.; Sokolovskyi, S.; Gozhenko, A.; Sobko, I.; Titov, G.; Gladyshev, V.; Khmil, M.; Kletnieks, Ugis (Journal of Education, Health and Sport, 2025)
The present paper aims to provide an overview of the use of biologically active components derived from mineral, synthetic, phyto-, and organic sources in the development of local hemostatic agents. The study highlights the historical and contemporary use of these agents in medical practice, and examines the scientific evidence supporting their efficacy. Hemostasis, the process of stopping bleeding, is a critical component of surgical and medical procedures. Local hemostatic agents are widely used to achieve hemostasis in a targeted and controlled manner, thereby minimizing the risk of complications associated with bleeding. The use of biologically active components derived from various sources, including minerals, synthetic materials, plants, and organic compounds, has a long history in the development of hemostatic agents. These components can act through various mechanisms, such as inducing platelet aggregation, activating the coagulation cascade, or promoting the formation of blood clots. Recent advances in biotechnology and nanotechnology have led to the development of novel hemostatic agents with improved properties, such as enhanced biocompatibility, targeted delivery, and controlled release. These agents have the potential to revolutionize hemostasis in surgical and medical procedures, and improve patient outcomes. Overall, the study highlights the importance of biologically active components derived from mineral, synthetic, phyto-, and organic sources in the development of local hemostatic agents. The review of historical and contemporary use of these agents underscores their continued relevance in medical practice, while recent advances in technology offer exciting new possibilities for future development. After a thorough review of domestic and foreign literature, the development team used adsorbing materials from biologically active components of mineral, synthetic, phyto-, and organic origin to create a hemostatic powder known as "PLANTOR." The active components of PLANTOR include aerosol, carrageenan of a special brand, and a specific mixture of medicinal vegetable oils, which have a special sorption effect. Due to the well-selected composition of the product, PLANTOR forms a blood clot in the wound through a biophysical process of liquid absorption. Notably, PLANTOR does not contain procoagulant minerals or nanoparticles that could remain in the human body, and therefore does not belong to means with a chemical or biochemical mechanism of action. Based on the above, it is possible to recommend the hemostatic agent-powder "PLANTOR" of the trade mark "PLANTOR tm" and "Dr. Sokolovskiy R" of the manufacturer "Medpro Nutraceuticals" (Latvia) by order of LLC "Plantor" (Ukraine, Dnipro), the author and owner of the developed technology of the hemostatic agent - powder "PLANTOR" (TU U 20.4-44827581-001:2022) as an auxiliary means of revitalization, local coagulation, treated wound surfaces during emergency medical care for external bleeding.